2013
DOI: 10.1111/1574-6941.12179
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and potential activity of denitrifiers and methanogens in groundwater at 140 m depth in Pliocene diatomaceous mudstone of northern Japan

Abstract: Anaerobic microbial activity has a major influence on the subsurface environment. We investigated the denitrification and methanogenesis in anoxic groundwater at a depth of 140 m in two boreholes drilled in a sedimentary geological setting, where the redox potential fluctuated. The average maximum potential denitrification rates, measured under anaerobic conditions in the two boreholes using an (15) N tracer, were 0.060 and 0.085 nmol (30) N2  mL(-1)  h(-1) . The deduced NirS amino acid sequences obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 56 publications
0
3
1
Order By: Relevance
“…The occurrence of the nirS gene in g-proteobacteria has been reported recently (Katsuyama et al, 2013), but such large proportion of the nirS gene-carrying denitrifier from g-proteobacteria, as we found in this study, has never been reported before. We also detected nirS gene-carrying denitrifiers belonging to the Actinobacteria; this has only been reported in an aquatic environment (Li et al, 2012).…”
Section: Impact Of N Management On the Composition Of Denitrifying Bacontrasting
confidence: 49%
“…The occurrence of the nirS gene in g-proteobacteria has been reported recently (Katsuyama et al, 2013), but such large proportion of the nirS gene-carrying denitrifier from g-proteobacteria, as we found in this study, has never been reported before. We also detected nirS gene-carrying denitrifiers belonging to the Actinobacteria; this has only been reported in an aquatic environment (Li et al, 2012).…”
Section: Impact Of N Management On the Composition Of Denitrifying Bacontrasting
confidence: 49%
“…phylum Zixibacteria, formerly RBG-1 (one-way ANOVA post hoc test, p < 0.05, n = 48 for MM, n = 3 for TM, and n = 12 for OS; Supplementary Table S4) that has been identified as the dominant microorganisms in aquifer sediments and has the ability to assimilate ammonium (Castelle et al, 2013). Previously, the deep continental biosphere was suggested to be mainly supported by sulfate reduction (Nielsen et al, 2006; Hallbeck and Pedersen, 2008; Katsuyama et al, 2013). However, although nitrate, nitrite, and ammonium concentrations were very low in this oligotrophic subsurface environment and regardless of their ultimate source (Swanner and Templeton, 2011), this study also supports that nitrogen cycling may be important for the microorganisms inhabiting the deep biosphere (Kutvonen et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Others variables such as NO 3 -concentration, nutrients, pH, and microbial acclimation only exert secondary influences on denitrification rate in aquifers [29]. In the case of aquifer in Miyakonojo Basin, although denitrifiers were found in the oxic sample Md-5, the denitrification process could not proceed due to 5.9 mg/L oxygen [29,30]. Conversely, as for sample K-3, the presence of denitrifiers and the anoxic environment could support the occurrence of the denitrification process.…”
Section: Distribution Of Denitrifiers and Their Associations With Hydmentioning
confidence: 99%